VARK LEARNING STYLES AND SOCIAL MEDIA USAGE IN EFL CONTEXTS: INSIGHTS FROM TERTIARY-LEVEL STUDENTS - Saputra, Bima Eza; Dewi, Dian Novita (English Review: Journal of English Education, 2024)
The integration of social media into EFL learning has become increasingly popular, fostering greater student engagement, collaboration, resource innovation, and personalized learning experiences. This study examines the usage patterns of social media and their alignment with VARK (Visual, Auditory, Read/write, Kinesthetic) learning style among tertiary-level EFL students in the English Language Education Study Program at Universitas Brawijaya. Utilizing a quantitative survey design, data were gathered from 100 undergraduate students of the 2023 cohort, all of whom had used social media for EFL learning for over a year. Analysis through Statistical Package for the Social Sciences (SPSS) and Microsoft Excel revealed that audio-based platforms, such as those featuring English songs and podcasts, are particularly favored by auditory, kinesthetic, and auditory-kinesthetic learners. YouTube emerged as the most preferred platform, with the highest mean score (3.64), selected by 31% of respondents. However, the findings indicate that students' social media preferences for EFL learning do not always align with their individual learning styles, suggesting a disconnect between preferred platforms and learning modalities. The study underscores the importance of selecting appropriate social media platforms tailored to diverse learning preferences in EFL education. These findings can guide educators in designing more effective EFL teaching strategies, leveraging the potential of social media to meet varying learner needs.